DETERMinants of quality of life, care and costs, and consequences of INequalities in people with Dementia and their carers (DETERMIND): A protocol paper. (25th December 2019) - Farina, Nicolas; Hicks, Ben; Baxter, Kate; Birks, Yvonne; Brayne, Carol; Dangoor, Margaret; Dixon, Josie; Harris, Peter R.; Hu, Bo; Knapp, Martin; Miles, Eleanor; Perach, Rotem; et al.
Abstract : Objectives: DETERMIND (DETERMinants of quality of life, care and costs, and consequences of INequalities in people with Dementia and their carers) is designed to address fundamental, and, as yet unanswered questions about inequalities, outcomes and costs following diagnosis with dementia. These answers are needed to improve the quality of care and equity of access to care, and therefore the quality of life, of people with dementia and their carers. Method: DETERMIND is a programme of research consisting of seven complementary workstreams (WS) exploring various components that may result in unequal dementia care: WS1: Recruitment and follow‐up of the DETERMIND cohort—900 people with dementia and their carers from three geographically and socially diverse sites within six months following diagnosis, and follow them up for three years. WS2: Investigation of the extent of inequalities in access to dementia care. WS3: Relationship between use and costs of services and outcomes. WS4: Experiences of self‐funders of care. WS5: Decision‐making processes for people with dementia and carers. WS6: Effect of diagnostic stage and services on outcomes. WS7: Theory of Change informed strategy and actions for applying the research findings. Outcomes: During the life of the programme, analysing baseline results and then follow‐up of the DETERMIND cohort over 3 years, we will establish evidence on current services and practice. DETERMIND will deliver novel, detailed data on inequalities in dementia care and what drives positive and negative outcomes and costs for people with dementia and carers, and identify factors that help or hinder living well with dementia.